Pressure Regulated Volume Control (PRVC): Set it and forget it? - Gurkeerat Singh (Respiratory Medicine Case Reports, 2020)
Pressure-regulated volume control (PRVC) is a mode of ventilation in which the ventilator attempts to achieve set tidal volume at lowest possible airway pressure. This mode of ventilation is being commonly used as the initial mode of ventilation in many intensive care units. We describe two cases where this adaptive mode of ventilation became maladaptive leading to patient-ventilator dyssynchrony.